(untitled) (Jurnal ForestrIndo, 2025)
Biomass is a renewable alternative energy source with abundant potential. The weakness of biomass as an energy material is its very diverse nature and lower calorific value compared to fossil-based energy. Pyrolysis is one of the energy conversion methods with the aim of increasing energy density with various forms of energy. This study aims to analyze seven bamboo species as energy materials with proximate analysis, and the pyrolysis was applied to increase their calorific value. Pyrolysis was carried out at a temperature of 350 °C for one hour and the characterization of bamboo and charcoal products was carried out with proximate analysis. The results showed that bamboo has the potential for biomass energy materials with an average calorific value of the seven bamboo species studied of 3941 kcal/kg (3869–4327 kcal/kg) with an average level of fixed carbon, volatile matter, and ash of 24.39%, 73.24%, and 2.37%, respectively. Pyrolysis increased the average calorific value by 70.34% from an average of 3941 kcal/kg of bamboo to an average of 6713 kcal/kg of their char. The increase in the calorific value of the char was mainly related to an increase in the average bound carbon content by 50.27% and a decrease in the average volatile matter content by 70.34%. Based on calorific value and ash conten; betung, gombong, and mayan bamboos meet the requirements as biomass energy materials according to SNI 8951:2020.